Education on Clean and Healthy Lifestyle and Use of Masks in the Praingu Prailiu Tourism Village, East Sumba - Wanti, Wanti; Gunawan, Yosephina Elizabeth Sumartini; Yurissetiowati, Yurissetiowati (Research and Social Study Institute, 2022)
A tourist village is a rural area that has a variety of tourist attractions. One of the tourism potentials that is the center of attention of tourists is the tourism potential on Sumba Island. One of the tourism potentials in East Sumba is Raja Prailiu Village, which is located in Prailiu Village, Kambera District, East Sumba Regency. Since the Covid-19 pandemic, the number of tourists, both domestic and foreign, has decreased so that the income of people in the area has decreased. The government is currently preparing to develop a strategy to change the status of the Covid-19 pandemic to endemic. This was welcomed by the local community so that preparations were needed to support the government's discourse. The purpose of this activity is to provide education about clean and healthy living behavior (PHBS) and how to use masks as an effort to prepare for the reopening of tourist villages in the area. This community service method involves 35 weavers and is implemented in the Traditional Village of Praingu Prailiu Village. The results of this activity increased the knowledge of respondents about clean and healthy living behavior and how to use masks properly and correctly. In conclusion, after giving lectures / counseling as many as 71.4% of respondents have good knowledge about a clean and healthy lifestyle, and 100% of respondents understand how to use masks properly and correctly.